2016
DOI: 10.1097/md.0000000000002869
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Influenza Vaccine Strain Was Effective in Reducing the Risk of Acute Myocardial Infarction in Elderly Persons

Abstract: The aim of this study was to explore whether matched or mismatched strains of influenza vaccines (IVs) are beneficial at reducing the risk of acute myocardial infarction (AMI) in elderly persons.Data were obtained from the Longitudinal Health Database 2005 (LHID 2005) which is maintained by the National Health Insurance Research Institute in Taiwan. The analytical data included individuals who were vaccinated with mismatched vaccines during the October 2007 to December 2007 season and individuals vaccinated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Gurfinkel and colleagues reported a significant reduction of the risk of death and ischemic events in patients suffering from CVD following a single intramuscularly dose of influenza vaccination 23 . In the case of AMI, the effectiveness of influenza vaccination was reported to be between 19 and 45% based on relevant studies 24 , 25 . The results of Wu et al, the study confirmed the beneficial role of influenza vaccination in reducing the risk of CVDs in elderly patients with previous myocardial infarction 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gurfinkel and colleagues reported a significant reduction of the risk of death and ischemic events in patients suffering from CVD following a single intramuscularly dose of influenza vaccination 23 . In the case of AMI, the effectiveness of influenza vaccination was reported to be between 19 and 45% based on relevant studies 24 , 25 . The results of Wu et al, the study confirmed the beneficial role of influenza vaccination in reducing the risk of CVDs in elderly patients with previous myocardial infarction 26 .…”
Section: Discussionmentioning
confidence: 99%
“…There are many contrasting ideas on the effectiveness of influenza vaccination on CVDs events. On the one hand, some observational studies demonstrate a positive relationship between influenza vaccination and a reduced incidence of cardiovascular events such as acute myocardial infarction (AMI) 5 , 6 . On the other hand, some epidemiological studies indicate that influenza vaccines do not have much effect 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical reports have shown that influenza vaccination reduces influenza-associated cardiovascular events (4,36,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Gwini et al identified that the influenza vaccine-induced protective effect is greater in those receiving the vaccine before mid-November (49).…”
Section: Association Between Influenza Virus Infection and Cardiovascmentioning
confidence: 99%
“… 33 Moreover, clinical evidence indicates that influenza vaccination may protect against acute myocardial infarction. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%